1987
DOI: 10.1002/ijc.2910400110
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐proliferative effects of interferons on Daudiburkitt Lymphoma cells: Induction of cell differentiation and loss of response to autocrine growth factors

Abstract: Treatment of Daudi B-lymphoblastoid cells with low concentrations of either natural or recombinant human alpha-interferons inhibits cell proliferation and modulates the expression of a number of cell-surface antigens. Using a panel of monoclonal antibodies (MAbs) identifying determinants expressed at the surface of normal plasma cells, and polyclonal antibodies against surface and cytoplasmic immunoglobulin, we have found that growth inhibition is accompanied by plasmacytoid differentiation. Assays of growth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
(16 reference statements)
1
16
0
Order By: Relevance
“…For initial experiments, we chose the highly IFN-␣-sensitive, EBV-positive BL line Daudi (29), in which IFN-␣ treatment inhibits cell proliferation and concomitantly induces plasmacytoid differentiation (8). Daudi cells were treated with different concentrations of IFN-␣, IFN-␤, and IFN-␥ (Peprotech) for 24 h, and the level of LMP-1 protein was analyzed by Western blotting (Fig.…”
mentioning
confidence: 99%
“…For initial experiments, we chose the highly IFN-␣-sensitive, EBV-positive BL line Daudi (29), in which IFN-␣ treatment inhibits cell proliferation and concomitantly induces plasmacytoid differentiation (8). Daudi cells were treated with different concentrations of IFN-␣, IFN-␤, and IFN-␥ (Peprotech) for 24 h, and the level of LMP-1 protein was analyzed by Western blotting (Fig.…”
mentioning
confidence: 99%
“…IFN has been reported to promote growth arrest and differentiation in some cells (10,33,38) and inhibit differentiation in others (16,42 (29,30). These observations, coupled with the findings of others, have led us to suggest that IFN has a regulatory role during the differentiation processes (29,30).…”
Section: Discussionmentioning
confidence: 75%
“…PIC (150 ng/ml) was added as indicated. Lanes 6 to 11 are phosphatase assays in which dsl was prephosphorylated for 10 kinase autophosphorylation and eIF-2ao phosphorylation are inhibited; however, if dRF is added to preactivated kinase (lane 9), dsl is not dephosphorylated, remains active, and is able to phosphorylate eIF-2o. These results indicate that the inhibition of dsl activity (eIF-2a phosphorylation) by dRF is a consequence of the inhibition of dsl activation (autophosphorylation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important biological property of interferons (IFNs) is their ability to inhibit the proliferation of many cell types in culture and in vivo (Hattori et al 1983 ; Clemens and Mcnurlan 1985 ;Exley 1987 et al). It has been clearly demonstrated that treatment of sensitive cells with IFNs alters the pattern of gene expression in many different cell types and brings about phenotypic changes (Weil et al 1983 ;Guardini et al 1984).…”
mentioning
confidence: 99%